Legal Protection for Endogamous Marriages of The Ahmadiyya Congregation in Manislor Village: A Perspective of Law No. 1 of 1974 - Indah Dwi Nurhidayah; Achmad Kholiq; Akhmad Khalimy (UIN Siber Syekh Nurjati Cirebon, 2026)
Administrative and social issues in the registration and recognition of endogamous marriages of the Ahmadiyya Community in Manislor Village reflect tensions between state legal norms and socio- religious conditions. According to Law Number 1 of 1974, the validity of a marriage is determined by the applicable religious law and must be registered to ensure legal certainty. However, in practice, the Ahmadiyya Community of Manislor Village faces administrative and social problems related to marriage registration. This study aims to analyze the conformity of the endogamous marriage practices of the Ahmadiyya Community with national legal regulations and to evaluate the importance of legal protection that the state should provide. Using a juridical-sociological and qualitative approach, this research employs a statutory and empirical framework, supported by field data collected in Manislor Village. The results of the study show that, normatively, there is no explicit prohibition on endogamy, but weak enforcement and a mismatch between law and social practice create legal uncertainty. This study concludes that legal protection is needed not to legitimize certain religious teachings, but to ensure citizens' constitutional rights to recognition and legal certainty in family life. This research contributes by formulating a non-discriminatory administrative framework in marriage registration for religious minority groups based on the theory of legal pluralism. Keywords: Endogamous Marriage; Ahmadiyya Congregation; Marriage Law